Seismic spectral monitoring of CO2 in a geological reservoir - Gómez, Julián Luis (2013)
Peak frequency is a spectral seismic attribute widely used for reservoir thickness estimation and hydrocarbon detection. In this work we apply this attribute in the context of the geological storage of carbon dioxide (CO2) and analyze its reliability as a thickness estimator for the gas accumulation. To model the vertical distribution of CO2, we solve the Buckley-Leverett equation with discontinuous flux function. A matrix reflectivity algorithm then computes, in the frequency domain, the seismic reflectivity. We find that the peak frequency variability due to CO2 saturation does not alter significantly its correlation with the accumulation thickness. We then extend the applicability of the spectral attribute by examining its time-lapse response to the evolution of the injected CO2 volume within a reservoir. We find that a description of the CO2-brine contact as well as the evaluation of the reservoir’s caprock sealing capacity can be obtained from this implementation. Peak-frequency time-lapse signatures when the CO2 forms an up-going front, evolves into a growing accumulation and leaks into the caprock are identified.